PHOTON PAIR PRODUCTION BY EPSILON+EPSILON- ANNIHILATION AND SEARCH FOR SUPERSYMMETRIC PHOTINOS AT ENERGIES GREATER THAN 40 GEV - Althoff, M; Braunschweig, W; Kirschfink, F; Lubelsmeyer, K; Martyn, H; Rosskamp, R; Schmitz, D; Siebke, H; Wallraff, W; Eisenmann, J; Fischer, H; Hartmann, H; et al. (Springer-Verlag, 1984)
The cross section for the process e+e-→γγ has been measured for c.m. energies 39.5<w<46.8 agreement="" and="" cut-off="" for="" found="" gev.="" good="" limits="" lower="" of="" parameters="" predictions="" qed="" the="" was="" with="" λ+="">61 GeV and Λ+> GeV (95% confidence level) have been determined. A search for two photon final states with missing energy provided lower limits on the masses of the photino and selectron. © 1984 Springer-Verlag.</w<46.8>